Effect of contact angles on polydimethylsiloxane (PDMS) microfludic capillary biosensors - Seah, Puay Kun. (2012)
In order to improve the sensitivity of the PDMS microfluidic capillary biosensor, there was a need to study methods to increase the capillary action of DI water such that the height difference is visible by naked eyes. The height difference between the DI water levels in two micro-channels, which was part of PDMS microfluidic capillary biosensor, was needed to determine the presence of enolase. This could be done by increasing the hydrophilicity of the walls of the micro-channels in the biosensor. This project was aimed to determine the contact angle on various surfaces of modified PDMS, especially on the modified PDMS with anti-enolase and immobilised enolase. Furthermore, modifying the surface of PDMS using oxygen plasma treatment, aminopropyltriethoxysilane (APTES), glutaraldehyde (GA) to improve the hydrophilicity and immobilisation of anti-enolase and enolase was analysed. On the whole, the oxygen plasma treated surface was the most hydrophilic with a contact angle of 58.1° and bare PDMS surface was the most hydrophobic with a contact angle of 109.7 °. In addition, studies on the effect of contact angle on the height of the DI water level in a PDMS capillary micro-channel and the height difference of DI water between two micro-channels due to immobilisation of enolase by calculation was done. This was needed to predict the dimensions of the micro-channels to ensure their length could be easily fabricated by lithography with radius that could result in obvious height difference of DI water. The dimension of the cuboid micro-channel, which was found by calculation, was fixed at w_B = 0.3698 mm, corresponding to the r_B= 0.235 mm, with a height of 20 mm.